2018
DOI: 10.1021/acsinfecdis.8b00182
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography Imaging with 2-[18F]F-p-Aminobenzoic Acid Detects Staphylococcus aureus Infections and Monitors Drug Response

Abstract: Staphylococcus aureus is the leading cause of life-threatening infections, frequently originating from unknown or deep-seated foci. Source control and institution of appropriate antibiotics remain challenges, especially with infections due to methicillin-resistant S. aureus (MRSA). In this study, we developed a radiofluorinated analog of para-aminobenzoic acid (2-[18F]F-PABA) and demonstrate that it is an efficient alternative substrate for the S. aureus dihydropteroate synthase (DHPS). 2-[18F]F-PABA rapidly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 45 publications
1
75
0
Order By: Relevance
“…A radiofluorinated analogue of p-aminobenzoic acid (m-[ 18 F]-fluoro-PABA) (Scheme 7), which is a substrate for folic acid synthesis in prokaryotes [93], was evaluated in rats infected with methicillin-resistant or -sensitive S. aureus [94]. Bacteria use folic acid for their synthesis of nucleic acids.…”
Section: Imaging the Folic Acid Synthesis Pathwaymentioning
confidence: 99%
“…A radiofluorinated analogue of p-aminobenzoic acid (m-[ 18 F]-fluoro-PABA) (Scheme 7), which is a substrate for folic acid synthesis in prokaryotes [93], was evaluated in rats infected with methicillin-resistant or -sensitive S. aureus [94]. Bacteria use folic acid for their synthesis of nucleic acids.…”
Section: Imaging the Folic Acid Synthesis Pathwaymentioning
confidence: 99%
“…The polymyxin B is an antibiotic, usually used for multidrug-resistant Gram-negative bacteria, that acts like an amphipathic antimicrobial peptide. Similarly, D-amino acids, molecules targeting the folate pathway in bacteria and siderophores have also been studied as bacterial specific imaging agents [34][35][36][37][38][39].…”
Section: Imaging Bacteria In Animal Modelsmentioning
confidence: 99%
“…PET study with m-[18F]-fluoro-PABA showed rapid uptake in bacterial infections (core to muscle ratio ≈ 8) and low uptake in sterile inflammation (about nine times lower), which meant that this radiopharmaceutical can be considered as specific for imaging bacterial infections. m-[18F]-fluoro-PABA showed reduced uptake in tissues infected with Staphylococcus aureus treated with oxacillin, indicating the possibility of using this radiopharmaceutical also to monitor response to treatment [42].…”
Section: Future Directionsmentioning
confidence: 99%